Propagation of ULF waves from the upstream region to the midnight sector of the inner magnetosphere. Issue 9 (10th September 2016) - Takahashi, Kazue; Hartinger, Michael D.; Malaspina, David M.; Smith, Charles W.; Koga, Kiyokazu; Singer, Howard J.; Frühauff, Dennis; Baishev, Dmitry G.; Moiseev, Alexey V.; Yoshikawa, Akimasa
Abstract: Ultralow frequency (ULF) waves generated in the ion foreshock are a well‐known source of Pc3‐Pc4 waves (7–100 mHz) observed in the dayside magnetosphere. We use data acquired on 10 April 2013 by multiple spacecraft to demonstrate that ULF waves of upstream origin can propagate to the midnight sector of the inner magnetosphere. At 1130–1730 UT on the selected day, the two Van Allen Probes spacecraft and the geostationary ETS‐VIII satellite detected compressional 20 to 40 mHz magnetic field oscillations between L ∼ 4 and L ∼ 7 in the midnight sector, along with other spacecraft located closer to noon. Upstream origin of the oscillations is concluded from the wave frequency that matches a theoretical model, globally coherent amplitude modulation, and duskward propagation that is consistent with expected entry of the upstream wave energy through the dawnside flank under the observed interplanetary magnetic field. The oscillations are attributed to magnetohydrodynamic fast‐mode waves based on their propagation velocity of ∼300 km/s and the relationship between the electric and magnetic field perturbations. The magnitude of the azimuthal wave number is estimated to be ∼30. There is no evidence that the oscillations propagated to the ground in the midnight sector. Key Points: Compressional Pc3 waves were detected in the magnetosphere both on the dayside and nightside with global coherence in amplitude modulation Phase delay analysis using three spacecraft in the midnight sector indicates duskward propagation of the waves The oscillations are attributed to fast‐mode waves originating from ULF waves generated in the ion foreshock